Utilization of Animals as Traditional Medicine in Pangkalpinang City, Bangka Island, Sumatra - SYAFUTRA, RANDI; PANITA, SHAKILA; FELICIA, TALITHA SISY; NUGROHO, RAMADHAN ARYO; APRIANTO, YORDI (Lembaga Penelitian, Pengabdian Kepada Masyarakat dan Kepustakaan, 2024)
Utilizes animals as traditional medicine have been known globally. A study to collect, analyze and evaluate utilization of animals as traditional medicine by indegenous people was carried in September to November 2022 in Pangkal Pinang City, Bangka Island, Sumatra. Data collection was done through surveys and informant selection using snowball sampling. Three selected local people were then interviewed according to the prepared questionnaire. We analysis information by qualitatively (using descriptive statistics) and quantitatively (calculating RFC or Relative Frequency of Citation) and Informant Consensus Factor (ICF). Our study found that the utilization of animals as traditional medicine is still practiced due to various interconnected reasons. The animals utilized as traditional medicine by local people consist of 6 families and 6 species, including Reptilia (3 species with a percentage of 50.0%), as well as Mammalia, Actinopterygii, and Aves (each with 1 species and a percentage of 16.7%). Herpetofauna ranks first based on the percentage of the number of animal species utilized as traditional medicine by the community of Ketapang Subdistrict. There is correlation between the age of informants and the level of knowledge regarding the utilization of animals as traditional medicine indicates that informants aged over 45 have broader knowledge due to their life experiences. Finally, wildlife conservation in traditional medicinal practices is essential to preserve cultural heritage and support ecological sustainability